Influence of Education Levels Based on Gender on Decision-Making Process in Deposit Taking Saccos in Uasin Gishu County, Kenya - publisher, publisher; Chelimo , Sarah (African Journal of Education,Science and Technology (AJEST), 2023)
Women in decision-making positions play a crucial role in developing meaningful gender mainstreaming strategies. Gender equity is a major factor in achievement of socio-economic and political development. The aim of this study was to examine the influence of education levels based on gender on decision-making process in deposit taking Saccos in Uasin Gishu County, Kenya. The study used cross-sectional research design and targeted 11 managers and 867 delegates. A sample size of 266 delegates and 11 managers was used in the study. Proportionate and simple random sampling was used to select delegates while purposive sampling was used to select the managers. The study used questionnaires and interviews to collect data. A pilot study was carried out in SACCOs in Trans-Nzoia County which has similar characteristics as the study area. Validity was determined by consulting research supervisors to improve data collection tools. Reliability was determined through the use of Cronbach Alpha. The quantitative data was analysed descriptively by SPSS (version 25) and the findings presented using frequencies and percentages. Pearson Correlation analysis was employed to determine relationship that exists between the independent and dependent variables. Qualitative data was thematically classified and arranged before they were reported in narrations and quotations. The study found out that there was a significant positive correlation between women’s education levels and decision-making process (r = .372; p = .000). The paper concluded that enhanced education levels among women positively affect decision making in deposit taking Saccos. It was recommended that there is need for deposit taking Saccos to recommend women with diverse education levels to be appointed to decision making bodies.